Solve for \( x \) : \[ 3 x-5=-x+3 \]
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To solve for \( x \), let's first get all the \( x \) terms on one side of the equation and the constant terms on the other side. We can start by adding \( x \) to both sides: \[ 3x - 5 + x = -x + 3 + x \] This simplifies to: \[ 4x - 5 = 3 \] Next, let's add \( 5 \) to both sides to isolate the term with \( x \): \[ 4x = 3 + 5 \] This gives us: \[ 4x = 8 \] Now, we can divide both sides by \( 4 \) to solve for \( x \): \[ x = \frac{8}{4} = 2 \] So, the solution is \( x = 2 \).